Biochemical investigations of hyperhomocysteinemia - Betts, Mary Victoria (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2000)
Hyperhomocysteinemia, a condition where plasma homocysteine occurs at an abnormally elevated level, is a common finding in vascular disease subjects. Several genetic and nutritional factors have been implicated. The first part of this thesis describes attempts to investigate the cellular basis for the accumulation of homocysteine seen in mild hyperhomocysteinemia. A method involving radiolabelling of methionine and its derivatives was designed to determine the fate of homocysteine in cells. It was hoped that such a system might provide insight into the factors that contribute to hyperhomocysteinemia. This study was carried out in nine control (non hyperhomocysteinemic) individuals and in seven vascular disease subjects, four of whom had mild hyperhomocysteinemia.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin